(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Сulture is a "living" category, whose development is directly related to the development of society. In this regard, the content of the socio-cultural component will constantly change, enriched with new content. An integral part of the linguoculturological component is a specially selected homogeneous language material that reflects the culture of the country of the language being studied, as well as nonequivalent background vocabulary, non-verbal languages of gestures, facial expressions and everyday behavior. Non-equivalent vocabulary occupies a special place. It exists because it denotes national realias. Knowing realias is important when studying the culture and language of the country. The presence of a national-cultural component, which is absent in other languages, remains a constant sign of the belonging of words to linguistic and cultural material.